2017
DOI: 10.15252/embj.201694700
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organized developmental patterning and differentiation in cerebral organoids

Abstract: Cerebral organoids recapitulate human brain development at a considerable level of detail, even in the absence of externally added signaling factors. The patterning events driving this self-organization are currently unknown. Here, we examine the developmental and differentiative capacity of cerebral organoids. Focusing on forebrain regions, we demonstrate the presence of a variety of discrete ventral and dorsal regions. Clearing and subsequent 3D reconstruction of entire organoids reveal that many of these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
262
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(289 citation statements)
references
References 42 publications
(69 reference statements)
26
262
1
Order By: Relevance
“…Regardless of LIF presence or absence, we did not detect signs of oligodendrocyte formation (Figure S4F). Long-term culture of organoids has previously been shown to result in glial overgrowth (Pasca et al, 2015; Renner et al, 2017), but we did not observe this to be the case in the W22 organoids. GFAP + astrocytes constituted ∼8% of the total cell population, less than that found in the human neonatal brain (∼40% GFAP+; Figures S5B-S5C).…”
Section: Resultscontrasting
confidence: 88%
“…Regardless of LIF presence or absence, we did not detect signs of oligodendrocyte formation (Figure S4F). Long-term culture of organoids has previously been shown to result in glial overgrowth (Pasca et al, 2015; Renner et al, 2017), but we did not observe this to be the case in the W22 organoids. GFAP + astrocytes constituted ∼8% of the total cell population, less than that found in the human neonatal brain (∼40% GFAP+; Figures S5B-S5C).…”
Section: Resultscontrasting
confidence: 88%
“…A recent study characterized cerebral organoids by demonstrating the presence of both distinct cerebral brain regions and forebrain organizing centres 56 . Immunohistochemical analyses revealed that several organoids contained a cell population that resembled the cortical hem, an important signalling centre implicated in forebrain patterning 57,58 .…”
Section: Organoids As Models Of Developmentmentioning
confidence: 99%
“…At the mid corticogenesis stage (7w+2d), FOXG1 is strongly expressed in the ventricular zone, the subventricular zone and the cortical plate (Onorati et al 2014), in a pattern that is similar to that observed in the mouse neocortex. Due to its restricted telencephalic expression in the neural tube, FOXG1 is frequently used as a marker in both mouse and human embryonic stems cell (ESC) and induces pluripotent stem cell (iPSC)derived telencephalic cell induction (Watanabe et al 2005;Eiraku et al 2008;Renner et al 2017).…”
Section: Expression Of Foxg1 In Vertebratesmentioning
confidence: 99%